Maintenance care in chiropractic – what do we know? - Leboeuf-Yde, Charlotte (BioMed Central, 2008)
BACKGROUND: Back problems are often recurring or chronic. It is therefore not surprising that chiropractors wish to prevent their return or reduce their impact. This is often attempted with a long-term treatment strategy, commonly called maintenance care. However, some aspects of maintenance care are considered controversial. It is therefore relevant to investigate the scientific evidence forming the basis for its use. OBJECTIVES: A review of the literature was performed in order to obtain answers to the following questions: What is the exact definition of maintenance care, what are its indications for use, and how is it practised? How common is it that chiropractors support the concept of maintenance care, and how well accepted is it by patients? How frequently is maintenance care used, and what factors are associated with its use? Is maintenance care a clinically valid method of approach, and is it cost-effective for the patient? RESULTS: Thirteen original studies were found, in which maintenance care was investigated. The relative paucity of studies, the obvious bias in many of these, the lack of exhaustive information, and the diversity of findings made it impossible to answer any of the questions. CONCLUSION: There is no evidence-based definition of maintenance care and the indications for and nature of its use remains to be clearly stated. It is likely that many chiropractors believe in the usefulness of maintenance care but it seems to be less well accepted by their patients. The prevalence with which maintenance care is used has not been established. Efficacy and cost-effectiveness of maintenance care for various types of conditions are unknown. Therefore, our conclusion is identical to that of a similar review published in 1996, namely that maintenance care is not well researched and that it needs to be investigated from several angles before the method is subjected to a multi-centre trial.